EVALUATION OF CARDIOVASCULAR AND PHARMACODYNAMIC EFFECTS OF TERMINALIA ARJUNA SINGLE DOSE AND MULTIPLE DOSE IN HEALTHY HUMAN MALES - Usharani, *Pingali; Fatima, Nishat; Ramakanth, Gadepalli; Muralidhar, Nizampatnam (International Journal of Ayurveda and Pharma Research, 2015)
Context: Terminalia arjuna is a medicinal plant used as a cardiotonic in Ayurveda. The presence of potent antioxidant constituents results in improvement in endothelial dysfunction seen in coronary artery disease. Aim: To evaluate the cardiovascular and pharmacodynamic effects of single and multiple doses of Terminalia arjuna in healthy human male subjects. Settings and Design: Randomized, double blind, placebo-controlled dose ranging study. Methods and Material: After approval from the institutional ethics committee, written informed consent was taken from subjects. Eligible subjects were allocated to the single and multiple dose groups, with six subjects in each group. The active treatment (Terminalia arjuna crude powder capsules of 500 mg, 1000 mg, 1500 mg & 2000 mg single dose and 1500 mg multiple dose) and placebo capsules were administered in 2:1 ratio in all the study groups. Vital parameters and pharmacodynamic assessment of cardiac profiling were performed using cold pressor test (CPT), tilt table and platelet aggregation tests. Statistical analysis used: The data was presented as mean ±SD. No statistical tests were applied as the sample size was less (n=6 in each group). Results: During CPT, Terminalia arjuna attenuated the rise in SBP, DBP and pulse rate in all the treatment groups compared to baseline. The CPT induced arterial stiffness was counteracted by treatment with 1500 mg & 2000 mg single dose and 1500 mg multiple doses of Terminalia arjuna. Cardiac output was increased with 1500 mg multiple dose at 600 tilt (Day 1) and at 450 & 600 phases of the tilt (Day 11). Platelet aggregation was markedly inhibited in 1500 mg multiple doses at Day 11. Conclusions: Treatment with single (1500 mg & 2000 mg) and multiple doses (1500 mg for 10 days) of Terminalia arjuna produced remarkable changes in the cardiovascular profile. Further studies in larger number of subjects and in patients with cardiovascular diseases are needed to confirm these effects.